An Overview and Proposed Research Framework for Studying Co-Occurring Mental- and Physical-Health Dysfunction. (July 2019) - Hagerty, Sarah L.; Ellingson, Jarrod M.; Helmuth, Timothy B.; Bidwell, L. Cinnamon; Hutchison, Kent E.; Bryan, Angela D.
Mental- and physical-health conditions co-occur at a rate much higher than chance. Of patients who have a mental-health condition, more than half also have a physical disease, and these cases are associated with increased human suffering and societal cost. Comorbidity research to date has focused on co-occurring mental- and physical-health disorders separately, and relatively little research has examined the co-occurrence of mental- and physical-health dysfunction. In addition, even less is known about why mental- and physical-health dysfunction co-occurs or how to treat these cases. Thus, the aims of this article are to highlight the need for research at the intersection of physical- and mental-health dysfunction and to provide guidance on how to research cases of comorbidity. Toward these ends, we begin by presenting a selective overview of the possible role of biological processes in the co-occurrence of physical- and mental-health dysfunction using specific illustrative examples. Specifically, we outline how biological processes within the immune system and gastrointestinal system could underlie depression, irritable bowel syndrome, and their co-occurrence. We then advance and discuss a proposed research framework, including methodological and analytic guidance, that researchers could use when studying the phenomenon of co-occurring physical- and mental-health dysfunction.